It's a matter of style: The role of audit firms and audit partners in key audit matter reporting - Rousseau, Linette M.; Zehms, Karla M. (Contemporary Accounting Research, 2024)
We examine the relative importance of audit firm versus partner decision styles in key audit matter (KAM) reporting. Standard setters intended KAMs to increase the usefulness of the audit report by requiring the partner‐led engagement team to disclose engagement‐specific information about the most significant judgments they made during the audit. However, stakeholders expressed widespread concern that audit firms' longstanding efforts toward standardization would result in generic KAMs at the audit firm level and provide partners little opportunity or incentive for engagement‐specific reporting. We evaluate this high‐stakes tension between standard setters' goals for audit reporting and auditors' deep‐rooted practices by leveraging data from the United Kingdom, which has required partner identification since 2009 and expanded audit reports since 2013. We find that clients sharing the same partner receive KAMs that are 10% more textually similar than clients with different partners. In contrast, clients sharing the same audit firm receive KAMs that are just 2% more textually similar than clients with different audit firms. This implies that partner decision styles are more important in influencing KAM outcomes than audit firm styles. Collectively, our results suggest that partners make unique KAM reporting judgments, countering concerns that audit firms' efforts toward standardization will yield boilerplate KAMs. This evidence extends the literature on expanded audit reporting and partner decision styles and provides valuable insights into a contemporary issue in audit regulation with broader implications for understanding dynamics within the profession.